IJTIHAD AS A SOURCE OF DYNAMICS ESTABLISHMENT OF ISLAMIC CULTURE - Enny Nazrah Pulungan; Ali Akbar (Fakultas Dakwah dan Komunikasi UIN Sumatera Utara Medan, 2022)
Ijtihad is the third pillar of Islam, after the Qur'an and Sunnah. The literal meaning of ijtihad is, that it comes from the word ijtahada, which means to devote energy, squeeze the mind, try hard, and work as much as possible. The message of Islam is a blessing for all nature, and a blessing for humans, how Islam guides human life which includes spiritual and physical aspects according to its message. In the worldly life of Muslims, it is necessary to formulate and enforce an Islamic cultural system that can create goodness for all human beings. A cultural system that must experience continuous development and progress as the nature of culture itself, which is always in tune with the spirit and demands of the times, but still with the breath of Islam. So, to face the changing life and answer every challenge of the times, Islam puts down a doctrine of free thought called ijtihad. If the Qur'an and Sunnah are the two basic sources of Islamic teachings, then ijtihad functions as a driving force.